Impact of Social Isolation on the Behavioral, Functional Profiles, and Hippocampal Atrophy Asymmetry in Dementia in Times of Coronavirus Pandemic (COVID-19): A Translational Neuroscience Approach - Muntsant, Aida; Giménez-Llort, Lydia (Frontiers in Psychiatry, 2020)
The impact of COVID-19 on the elderly is devastating, and nursing homes are struggling to provide the best care to the most fragile. The urgency and severity of the pandemic forces the use of segregation in restricted areas and confinement in individual rooms as desperate strategies to avoid the spread of disease and the worst-case scenario of becoming a deadly trap. The conceptualization of the post–COVID-19 era implies strong efforts to redesign all living conditions, care/rehabilitation interventions, and management of loneliness forced by social distance measures. Recently, a study of gender differences in COVID-19 found that men are more likely to suffer more severe effects of the disease and are over twice as likely to die. It is well-known that dementia is associated with increased mortality, and males have worse survival and deranged neuro-immuno-endocrine systems than females. The present study examines the impact of long-term isolation in male 3xTg-AD mice modeling advanced stages of Alzheimer's disease (AD) and as compared to age-matched counterparts with normal aging. We used a battery of ethological and unconditioned tests resembling several areas in nursing homes. The main findings refer to an exacerbated (two-fold increase) hyperactivity and emergence of bizarre behaviors in isolated 3xTg-AD mice, worrisome results since agitation is a challenge in the clinical management of dementia and an important cause of caregiver burden. This increase was consistently shown in gross (activity in most of the tests) and fine (thermoregulatory nesting) motor functions. Isolated animals also exhibited re-structured anxiety-like patterns and coping-with-stress strategies. Bodyweight and kidney weight loss were found in AD-phenotypes and increased by isolation. Spleen weight loss was isolation dependent. Hippocampal tau pathology was not modified, but asymmetric atrophy of the hippocampus, recently described in human patients with dementia and modeled here for the first time in an animal model of AD, was found to increase with isolation. Overall, the results show awareness of the impact of isolation in elderly patients with dementia, offering some guidance from translational neuroscience in these times of coronavirus and post–COVID-19 pandemic. They also highlight the relevance of personalized-based interventions tailored to the heterogeneous and complex clinical profile of the individuals with dementia and to consider the implications on caregiver burden.